Initial investigation of the corrosion stability of craniofacial implants - Beline, Thamara; Vechiato Filho, Aljomar Jose; Wee, Alvin G.; Sukotjo, Cortino; Santos, Daniela Micheline dos [UNESP]; Brandao, Thais Bianca; Ricardo Barao, Valentim Adelino (Elsevier B.V., 2018)
Statement of problem. Although craniofacial implants have been used for retention of facial prostheses, failures are common. Titanium undergoes corrosion in the oral cavity, but the corrosion of craniofacial implants requires evaluation. Purpose. The purpose of this in vitro study was to investigate the corrosion stability of commercially pure titanium (CP Ti) exposed to simulated human perspiration at 2 different pH levels (5.5 and 8). Material and methods. Fifteen titanium disks were divided into 3 groups (n=5 per group). The control group was subjected to simulated body fluid (SBF) (control). Disks from the 2 experimental groups were immersed in simulated alkaline perspiration (SA(K)P) and simulated acidic perspiration (SA(C)P). Electrochemical tests, including open circuit potential (3600 seconds), electrochemical impedance spectroscopy, and potentiodynamic tests were performed according to the standardized method of 3-cell electrodes. Data were analyzed by 1-way ANOVA and the Tukey honestly significant difference tests (alpha=.05). Results. Simulated human perspiration reduced the corrosion stability of CP Ti (P<.05). The SBF group presented the lowest capacitance values (P<.05). SA(K)P and SA(C)P groups showed increased values of capacitance and showed no statistically significant differences (P>.05) from each other. The increase in capacitance suggests that the acceleration of the ionic exchanges between the CP Ti and the electrolyte leads to a lower corrosion resistance. SA(K)P reduced the oxide layer resistance of CP Ti (P<.05), and an increased corrosion rate was noted in both simulated human perspiration groups. Conclusions. Craniofacial implants can corrode when in contact with simulated human perspiration, whereas alkaline perspiration shows a more deleterious effect. Perspiration induces a more corrosive effect than simulated body fluid.